2012
DOI: 10.1111/j.1365-2125.2011.04145.x
|View full text |Cite
|
Sign up to set email alerts
|

Methadone inhibits CYP2D6 and UGT2B7/2B4 in vivo: a study using codeine in methadone‐ and buprenorphine‐maintained subjects

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Although not well recognized, methadone inhibits CYP2D6 in vivo and in vitro and UGT2B7 and 2B4 in vitro.• We aimed to investigate the effect of methadone on the pathways of codeine metabolism, namely O-demethylation (CYP2D6), 6-glucuronidation (UGT2B4/7) and N-demethylation (CYP3A4/2C8), in subjects maintained on methadone or buprenorphine as a control. WHAT THIS STUDY ADDS• Compared with subjects on buprenorphine, methadone reduced the clearance of codeine to morphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
(55 reference statements)
3
12
0
2
Order By: Relevance
“…Inactive metabolites and some unmetabolized methadone are excreted in the bile and urine [64]. Although not normally thought of as an inhibitor, a recent in vivo study suggests that methadone is associated with inhibition of CYP 2D6 and UDP-glucuronosyl transferase (UGT) 2B4 and 2B7 [65]. The clinical significance of this inhibition is currently unknown.…”
Section: Overview Of Metabolism Of Methadonementioning
confidence: 99%
“…Inactive metabolites and some unmetabolized methadone are excreted in the bile and urine [64]. Although not normally thought of as an inhibitor, a recent in vivo study suggests that methadone is associated with inhibition of CYP 2D6 and UDP-glucuronosyl transferase (UGT) 2B4 and 2B7 [65]. The clinical significance of this inhibition is currently unknown.…”
Section: Overview Of Metabolism Of Methadonementioning
confidence: 99%
“…Nonetheless, this study further indicates that tramadol can be used safely in BMT patients for the treatment of acute and chronic pain. Our observations in MMT patients adds to our previous report that codeine is also unlikely to be an effective analgesic in MMT due to reduced CYP2D6‐mediated O‐demethylation of codeine to morphine and its glucuronides [22]. Therefore, it can be postulated that any opioid requiring O‐demethylation via CYP2D6 to produce an active metabolite will not provide adequate analgesia in MMT patients, so alternative analgesics that do not rely on CYP2D6 mediated metabolism need future consideration in this population.…”
Section: Discussionmentioning
confidence: 59%
“…With regard to tramadol use in opioid maintenance patients, there is potential for methadone to inhibit the formation of M1 due to its competitive inhibition of the CYP2D6-mediated O-demethylation of dextromethorphan [20,21]. This is supported by our recent study that demonstrated that methadone significantly inhibited the CYP2D6-mediated O-demethylation of codeine to morphine and its glucuronides [22]. Clinically, this has the potential to alter tramadol analgesia in a similar manner as paroxetine (a potent CYP2D6 inhibitor) that reversed tramadol analgesia to cold pressor pain [23].…”
Section: Introductionmentioning
confidence: 67%
“…This effect seems to be related to induction of CYP2B6 and CYP3A4 mRNA expression (Campbell et al, 2013) and may explain the requests for higher doses by some drug addicts (Horns et al, 1975). Moreover, another in vivo study demonstrated that methadone is associated with inhibition of CYP2D6 and UDP-glucuronosyl transferase (UGT) 2B4 and 2B7 (Gelston et al, 2012). The inhibitory effect on UGT2B7 is shown to have an important role in opiate withdrawal symptoms, including pupil size and tremor (Tian et al, 2012).…”
Section: Metabolismmentioning
confidence: 93%